Поняття процесуального представництва та його види - Мороз, О. В.; Moroz, O. V. (Право і суспільство. - 2023. - № 5. - С. 33-39, 2023)
Досліджено поняття процесуального представництва. Проаналізовано підходи до визначення процесуального представництва через правовідношення та через процесуальну діяльність представника. Вказано, що представництво пов’язане із наступними видами правовідносин: між представником і довірителем (внутрішні правовідносини), між представником та судом (зовнішні правовідносини) та між довірителем і судом. Визначено те, що основними цілями процесуального представництва виступає захист прав і охоронюваних законом інтересів учасників справи, та реалізація процесуальних прав й обов’язків учасників процесу.

The article analyzes the concept of procedural representation. Approaches to determining the concept of procedural representation in terms of legal relations and in terms of procedural activity of the representative are analyzed. It is pointed out that representation is related to the types of legal relations: between the representative and the principal (internal legal relations), between the representative and the court (external legal relations) and between the principal and the court. It was ascertained that the objectives of procedural representation are protecting the legal rights and interests of the participants of the case and implementing procedural rights and obligations of the participants in the process. It is indicated that the derivative goals of procedural representation are: assisting the court in administering justice, preventing violations of the procedural rights of the represented person, achieving the most favourable result for the represented person. The author agrees with the definition of procedural representation: procedural representation is the performance in a civil procedure of legal actions by one person (representative) on behalf of another person with the purpose of protecting his/her rights and legal interests or realizing his/her procedural rights or obligations. The article examines the rather controversial issue of dividing procedural representation into types. The analysis of procedural representation was carried out: due to the grounds of occurrence (legal and contractual); due to the method of occurrence (optional and mandatory); due to the characteristics of the persons whose interests are represented (representation of the parties, third parties, applicants, interested persons, state authorities, local self-government bodies); due to the basis of persons performing representation (representation performed by lawyers, legal advisers and other employees of organizations, parents, guardians, custodians, citizens, admitted by the court to represent a specific person in a specific case).

Исследовано понятие процессуального представительства. Проанализированы подходы к определению процессуального представительства через правоотношение и процессуальную деятельность представителя. Указано, что представительство связано со следующими видами правоотношений: между представителем и доверителем (внутреннее правоотношение), между представителем и судом (внешние правоотношения) и между доверителем и судом. Определено, что основными целями процессуального представительства выступает защита прав и охраняемых законом интересов участников дела, и реализация процессуальных прав и обязанностей участников процесса.
Keywords: представництво; representation; представительство; процесуальне представництво; procedural representation; процессуальное представительство; види процесуального представництва; types of procedural representation; виды процессуального представительства